Medullary Thyroid Carcinoma with Micronodular Lung Metastases: A Case Report with an Emphasis on the Imaging Findings - Nina Ventura; Edson Marchiori; Gláucia Zanetti; Antonio Muccillo; Mariana Leite Pereira; Guilherme Abdalla; Pedro Martins; Carolina Lamas Constantino; Rodrigo Canellas; Viviane Brandão; Romulo Varella de Oliveira (Case Reports in Medicine)
Medullary thyroid carcinoma is a rare malignancy that arises from calcitonin-producing C-cells and frequently metastasizes to lymph nodes in the neck. Distant metastases may involve bone, lung, and liver. The infrequent number of cases limits the clinical nature and ability to optimize diagnostic tools. Here, we present a case of a micronodular radiographic pattern in metastatic medullary thyroid cancer in order to enhance awareness of the disease process. A case discussion and relevant review of the literature are provided.